Zimbabwe’s post-2000 land reform programme, inter-ethnic hierarchies among ‘Black Zimbabweans’ and the potential of resource conflict: the case of Chipinge District - Terrence Musanga (Taylor and Francis Group, 2023)
This article examines the inter-ethnic hierarchies among ‘Black Zimbabweans’ and the potential of tension and conflict over land in Zimbabwe. The land reform programme executed in 2000, with the intention of restoring land to its ‘rightful’ owners (read blacks/Africans), has accentuated this tension and conflict. However, ‘black Zimbabweans’, irrespective of the Zimbabwe African National Union Patriotic Front’s (ZANU-PF) patriotic history and nationalist rhetoric of ‘sameness’ and ‘oneness’, are not monolithic as they are divided along class, ethnic and gender lines. This division is key in negotiating and accessing national resources such as land as it translates into ‘national cultural’ capital. Ethnic conflict and tension is rife in Zimbabwe and this makes it possible to consider the inter-ethnic dimensions of what it means to be a ‘black Zimbabwean’ and how this inter-ethnicity might have influenced or affected Zimbabwe’s land reform programme. I use the Ndau ethnic group of the Chipinge District as a case study as the majority of the Ndau feel marginalized in the allocation of redistributed A2 farms in Zimbabwe’s Natural Regions 1 and 2 chiefly characterised by dairy and agricultural farming. This marginalization disadvantaged them as it privileged ‘outsiders’ (read ‘other’ ethnic groups in Zimbabwe).